Comparative effects of sulfones and rifampin on growth of Mycobacterium lepraemurium in macrophage diffusion chamber cultures. - Rightsel, W A (1978)
A cell-impermeable diffusion chamber technique has been developed that lends itself to growth studies of Mycobacterium lepraemurium. This technique, in which the organism grows within macrophage cultures inside the chambers that are maintained on monolayer cultures of macrophages, provides a method for a strict in vitro evaluation of antileprosy drugs without the influence of a multiplicity of host factors. This system was used to compare the effect of three sulfone derivatives and rifampin on the growth of M. lepraemurium within these diffusion chamber cultures. Two sulfones, 4,4'-diaminodiphenyl sulfone and 4,4'-diacetamidodiphenyl sulfone, as well as rifampin, suppressed the growth of M. lepraemurium, but monoacetyl sulfone 4-amino-4'acetamidodiphenyl sulfone had no effect. The results indicate that the diffusion chamber technique can be used to evaluate the inhibitory effect of antileprosy drugs on the growth of M. lepraemurium. Also, the method provides for the first time a relatively rapid in vitro method for directly comparing the effects of drugs or their analogs when outside the metabolic influence of an animal host. This technique may be a useful tool for chemotherapy studies with other antileprosy compounds.